2011
DOI: 10.3324/haematol.2010.034447
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of high ABC transporter activity in 111 adult acute myeloid leukemia patients with normal cytogenetics when compared to FLT3, NPM1, CEBPA and BAALC

Abstract: Articles and Brief Reportshaematologica | 2012; 97(2) 241 IntroductionThe overall prognosis for adult acute myeloid leukemia (AML) remains poor. Cytogenetic analysis provides the major prognostic information, 1 but more than 40% of patients have normal cytogenetics (CN-AML). In these cases, many molecular alterations with prognostic significance have been described to guide treatment. Mutations involving nucleophosmin (NPM1) and the CCAAT/enhancer binding protein alpha (CEBPA) have been included as references … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 19 publications
3
15
0
1
Order By: Relevance
“…For example, selective toxicity of Dp44mT may be restricted to cells in which massive overexpression of Pgp results in lysosomal localization. This is relevant because clinical studies suggest that the expression of Pgp in tumor cells is far inferior to that observed in MDR cell lines (49,50). We have shown that the toxicity of NSC73306 is proportional to Pgp expression in a series of KB cells encompassing a wide range of Pgp expression levels (29).…”
Section: Discussionmentioning
confidence: 87%
“…For example, selective toxicity of Dp44mT may be restricted to cells in which massive overexpression of Pgp results in lysosomal localization. This is relevant because clinical studies suggest that the expression of Pgp in tumor cells is far inferior to that observed in MDR cell lines (49,50). We have shown that the toxicity of NSC73306 is proportional to Pgp expression in a series of KB cells encompassing a wide range of Pgp expression levels (29).…”
Section: Discussionmentioning
confidence: 87%
“…P-glycoprotein activity has thus been investigated in clinical samples from patients suffering from acute myeloid leukemia [135][136][137], acute lymphoblastic leukemia [138], B-cell chronic lymphocytic leukemia [139], myeloma [140] and lymphoma [141]. Data suggest a prognostic impact of P-glycoprotein activity in acute myeloid leukemias [142,143] but not in acute lymphoblastic leukemias [144]. Interestingly, the functional rhodamine 123-efflux assay should be preferred for flow-cytometric P-glycoprotein evaluation in acute leukemia compared with P-glycoprotein expression analysis by monoclonal antibodies [145].…”
Section: Analysis Of Drug Transporter Activity In Clinical Hematologimentioning
confidence: 99%
“…FLT3-ITD, NPM1 and CEBPA mutations were screened from fresh or frozen samples as previously described [19].…”
Section: Patients and Treatmentmentioning
confidence: 99%